Optimization of the Performance of Bhabinkamtibmas Through Guidance and Counseling to Prevent the Crime of Theft in the Jurisdiction of Polresta Magelang (Indonesian Journal of Police Studies, 2024)
The high population density in Magelang Regency with very few jobs creates potential disturbances, one of which is the crime of theft, so the presence of Bhabinkamtibmas is needed. Bhabinkamtibmas, which carries out a pre-emptive function in its duties to create conducive Kamtibmas, one of its efforts is the guidance and counseling method. From 2020 to 2021, cases of theft in the jurisdiction of the Magelang Police will increase, therefore there is a need for preventive action. In connection with the prevention carried out, the obstacle lies in the implementation of guidance and counseling carried out by Bhabinkamtibmas, there is still no material that focuses on the trend of crimes that are occurring so it is important to optimize Bhabinkamtibmas in preventing criminal acts of theft. The purpose of this study was to analyze the performance of Bhabinkamtibmas and the competence of Bhabin members in optimizing guidance and counseling to prevent criminal acts of theft. This study uses a qualitative approach with the Field Research method. Then, data sources were obtained from primary and secondary data sources with collection techniques through observation, interviews, FGDs, and document studies. Then, the correctness of the data was confirmed using data triangulation which was then analyzed using data reduction techniques, data presentation, and concluding. The results of the study found that the performance of Bhabinkamtibmas and the competence of Bhabinkamtibmas members were not optimal. So it is necessary to solve the problem in the form of improving the material, coordinating with cross-functions, proposing members to take part in Dikjur or Dikbangspes, conducting FGDs via Zoom meetings, making high achieving Bhabinkamtibmas posters, prioritizing the use of the BOS application, and utilizing the timestamp application in the reporting system.
Keywords: Bhabinkamtibmas, guidance, counselling, performance, theft